2021
DOI: 10.1007/s00330-021-08170-8
|View full text |Cite
|
Sign up to set email alerts
|

Signal intensity ratio of draining vein on silent MR angiography as an indicator of high-flow arteriovenous shunt in brain arteriovenous malformation

Abstract: Objectives To evaluate whether the signal intensity ratio (rSI) of the draining vein on silent MR angiography is correlated with arteriovenous (A–V) transit time on digital subtraction angiography (DSA), thereby identifying high-flow A–V shunt in brain arteriovenous malformation (BAVM), and to analyze whether the rSI and the characteristic of draining veins on silent MRA are associated with hemorrhage presentation. Methods Eighty-one draining veins of 46 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Our angiogram data suggested a fast inflow along with restricted venous outflow structure was predictive of future hemorrhage risk. The present study also confirmed a higher ratio of undilated draining vein with high signal intensity or fast flow though AVM lesion in ruptured AVM [2]. The fast flow through AVM nidus was found to be correlated with reduced mural cell coverage of AVM vessels and may contribute to vascular instability in AVM with hemorrhage [5].…”
supporting
confidence: 85%
See 2 more Smart Citations
“…Our angiogram data suggested a fast inflow along with restricted venous outflow structure was predictive of future hemorrhage risk. The present study also confirmed a higher ratio of undilated draining vein with high signal intensity or fast flow though AVM lesion in ruptured AVM [2]. The fast flow through AVM nidus was found to be correlated with reduced mural cell coverage of AVM vessels and may contribute to vascular instability in AVM with hemorrhage [5].…”
supporting
confidence: 85%
“…The fast flow through AVM nidus was found to be correlated with reduced mural cell coverage of AVM vessels and may contribute to vascular instability in AVM with hemorrhage [5]. This silent MRA study of AVM presented the relationship between venous signal intensity and the transit time through nidus [2], which supplement the spatial resolution of hemodynamic analysis on angiogram. However, it should be noted that the signal intensity and transit time were not derived from the same vascular segment, and the accurate meaning of signal intensity on silent MRA was not fully understood.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Intracranial vascular lesions encompass a broad spectrum of entities which differ in hemodynamic physiology, structure and prognosis [ 1 3 ]. They have been increasingly seen in clinical practice primarily because of new developments in imaging technology [ 4 ]. In recent years, an effort has been made to categorize these vascular anomalies, classified over the years in a variety of ways by many authors, often on the basis of blood flow patterns, amplified magnetic resonance imaging (MRI), angiography, histopathological features or demographics [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to sound reduction, silent MRA outperformed time-of-flight MRA (TOF-MRA) in visualizing flow in a small diameter, slow-flow, multidirectional flow, whirlpools, turbulent flow blood vessels, and flowing blood in stents or residual space in aneurysms after coiling 7. Consequently, silent MRA has been proven to better visualize unruptured aneurysms, Moyamoya vessels, brain arteriovenous malformations, intracranial dural arteriovenous fistulas, and follow-up after endovascular treatment of cerebral aneurysms than TOF-MRA 8–11. However, to date, the ability of silent MRA to reliably assess the three-dimensional (3D) morphology and hemodynamics of IAs remains unclear.…”
Section: Introductionmentioning
confidence: 99%